Shape effect on mixing and age distributions in service reservoirs. Issue 11 (1st November 2014) - Zhang, Jun‐Mei; Lee, Heow Pueh; Khoo, Boo Cheong; Peng, Kai Qi; Zhong, Liang; Kang, Chang‐Wei; Ba, Te
Abstract : Service reservoirs operate better with completed mixed flow to ensure uniform distributed disinfectant. In this article, the shape effect on mixing and age distributions of a service reservoir was investigated computationally by analyzing three service reservoirs that have commonly designed shapes (rectangle, square, and circle). With the use of the computational fluid dynamics (CFD) method coupled with dynamic meshes, realistic dynamic flow in the service reservoir was simulated with affordable computational cost. The water age distributions were predicted in detail by solving the age equation. Among the three investigated service reservoirs, the rectangular service reservoir had the smallest region of aged water in size and lowest volume‐averaged age values. This is reasonable because the outlet is located opposite to the inlet in this study, and the fluid mixes better along the jet trajectory by virtue of jet‐spreading and turbulent eddies. Therefore, a rectangular service reservoir is the best design among the three tanks investigated. The effects of thermal stratification, inlet–outlet layout, turnover, and height‐over‐diameter (H/D) ratio on mixing and age distributions are not fully covered in this work. The current approach, however, can still be employed to incorporate and evaluate each or combined mentioned effect(s) to arrive at the optimal reservoir design.